The 100: a ranking of the most influential persons in history - Hart, Michael H. (Golden Books Centre Kuala Lumpur, Malaysia, 1999)
The 100: A Ranking of the Most Influential Persons in History presents a list of individuals who significantly shaped human history, analyzing their impact across cultures and eras.